Frequency‐dependent top‐down modulation of temporal summation by anodal transcranial direct‐current stimulation of the primary motor cortex in healthy adults. (23rd May 2018) - Hughes, S.W.; Ali, M.; Sharma, P.; Insan, N.; Strutton, P.H.
Abstract: Background: Transcranial direct‐current stimulation (tDCS) applied over the primary motor cortex has been shown to be effective in the treatment of a number of chronic pain conditions. However, there is a lack of understanding of the top‐down analgesic mechanisms involved. Method: In this study, we investigated the effects of tDCS on the facilitation of subjective sensory and pain scores using a transcutaneous electrically evoked measure of temporal summation. In this randomized, blinded, cross‐over study healthy subjects received a single stimulus given at 0.9× pain threshold (pTh) over the L5 dermatome on the lateral aspect of the right leg, followed by a train of 5 stimuli given at 0.5, 1, 5 and 20 Hz before and after 20 min of sham or anodal tDCS (2 mA) applied over the primary motor cortex. Ratings of sensation and pain intensity were scored on a visual analogue scale (VAS). Results: Temporal summation leading to pain only occurred at higher frequencies (5 and 20 Hz). Sham or real tDCS had no effect over temporal summation evoked at 5 Hz; however, there was a significant analgesic effect at 20 Hz. Sham or real tDCS had no effect over acute, single stimuli‐evoked responses. Conclusion: These results indicate that anodal tDCS applied to the primary motor cortex preferentially modulates temporal summation induced by high‐frequency electrical stimulation‐induced pain. The inhibitory effects of tDCS appear to be dynamic and dependent on the degree of spinal cord excitability and may explain the higher analgesic efficacy in patients with moderate to severe chronic pain symptoms. Significance: The analgesic effects of tDCS are dependent on spinal cord excitability. This work provides insight into top‐down modulation during acute pain and temporal summation. This knowledge may explain why tDCS has a higher analgesic efficacy in chronic pain patients.